The Portable Fuel Transfer Pump Control System of Android Based for The Fuel Filling Effectiveness of Penerbad’s Helicopter - Nurcahyo, Nurcahyo; Syafaat, Mokhamad; Setiawan, Ade (Jurnal Elkasista, 2021)
Abstract – The task of Army Aviation Operations is carried out in remote areas where airport services are still minimal, the process related to refueling for pilot helicopters is an obstacle in carrying out the pilot's main tasks. So, we need tools to make the process more effective. This research uses a method that will obtain quantitative data for research to prove the hypothesis. The method is known as the Development Life Cycle Waterfall Diagram and experimental research. Currently still using a hand pump, therefore it is necessary to have a tool that is portable and uses an electric pump. specifically for fuel which is controlled by Arduino and the android application as input for a filling command and can store charging data. In this case the tool system uses supporting components, namely batteries, Bluetooth hc 05, 5v relays and flow sensors. With the research on portable pump tools, the process can be more efficient than hand pumps. When refueling the helicopter, it is enough to enter the charging value from the android application, the charging is already running, and the charging data is stored in the android file.